2015
DOI: 10.1111/rec.12281
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of forest restoration in an urban park

Abstract: Creating, restoring, and sustaining forests in urban areas are complicated by habitat fragmentation, invasive species, and degraded soils. Although there is some research on the outcomes of urban reforestation plantings during the first 5 years, there is little research on longer term outcomes. Here, we compare the successional trajectories of restored and unrestored forest sites 20 years after initiating restoration. The sites are located within the Rodman's Neck area of Pelham Bay Park, in the northeast corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 28 publications
1
22
0
3
Order By: Relevance
“…Creating new forests by planting trees in cities is well established in restoration ecology, e.g., [26][27][28][29], ranging from near-natural sites at the urban fringe, e.g., [30,31], to anthropogenically altered sites [32][33][34]. Yet such tree plantings and related maintenance require the allocation of considerable resources and do not always yield satisfying results, e.g., when continued maintenance is necessary [31,35]. It may thus be useful to consider complementary pathways towards establishing new forests in cities.…”
Section: Introductionmentioning
confidence: 99%
“…Creating new forests by planting trees in cities is well established in restoration ecology, e.g., [26][27][28][29], ranging from near-natural sites at the urban fringe, e.g., [30,31], to anthropogenically altered sites [32][33][34]. Yet such tree plantings and related maintenance require the allocation of considerable resources and do not always yield satisfying results, e.g., when continued maintenance is necessary [31,35]. It may thus be useful to consider complementary pathways towards establishing new forests in cities.…”
Section: Introductionmentioning
confidence: 99%
“…This is also because habitats that have been subjected to anthropogenic disturbance (e.g., agriculture) particularly in close proximity to cities are more vulnerable and highly likely to be invaded (e.g., [74]). Repeated removal of IAPs can increase native tree recruitment and tree species diversity [4]. Furthermore, past studies have found a decrease in IAP cover with an increase in natural forest tree canopy cover (e.g., [75]).…”
Section: Discussionmentioning
confidence: 99%
“…The colonization of reforested habitats by weeds (graminoids and forbs) and IAPs is a serious concern, because this can lead to restoration failure if weed/IAP management is inadequate/unsuitable [4,14]. It is therefore critical to continuously monitor the presence, expansion and distribution of IAPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Водночас, досі недостатньо оцінено вплив діяльності людини на рекреаційно-оздоровчі, захисні і природоохоронні деревостани міста на ландшафтно-екологічному рівні, хоча рекогносцирувальне обстеження території Умані і дослідження нами дендропарку "Софіївка" та урочища "Білогрудівська дача" свідчать, що вони є істотними (Lavrov et al, 2015(Lavrov et al, , 2017. Для збереження й оптимізації структури зеленої зони міста, підвищення її екологічної ефективності необхідно врахувати зазначені проблеми, а також наявний досвід щодо створення й утримання зелених насаджень у містах Європи та його використання в Україні (Laptiev, 1998;Kucheriavyi, 1999;Ricotta et al, 2009;Williams et al, 2015;Simmons et al, 2016;Rat et al, 2017). Це сприятиме ефективнішій реалізації "Програми благоустрою міста Умань на 2016-2020 роки".…”
unclassified